2018
DOI: 10.1007/s11011-018-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum levels and gene expression of tumor necrosis factor-α-induced protein-8 like-2 with Parkinson disease severity

Abstract: Different immune-mediated mechanisms involved in the pathogenesis of Parkinson disease (PD) as a neurodegenerative and inflammatory disease. According to our knowledge, there is no report evaluating Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2), a cytokine maintaining immune homeostasis, in PD. We analyzed the correlation of the serum levels and circulatory gene expression of TIPE2 with severity of PD. In this case-control study, 43 patients with PD and 40 healthy subjects were enrolled. The diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, Cystatin C was able to predict the severity of sleep-disordered breathing associated with PD [ 171 ]. Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2) has been postulated as a good prognosis biomarker [ 238 ]. However, other proteins such as DJ-1 were not considered good biomarkers since their levels did not differ between PD and HC [ 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Cystatin C was able to predict the severity of sleep-disordered breathing associated with PD [ 171 ]. Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2) has been postulated as a good prognosis biomarker [ 238 ]. However, other proteins such as DJ-1 were not considered good biomarkers since their levels did not differ between PD and HC [ 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…They further showed that enhanced serum levels of TIPE2 possess a direct correlation with age and severity of patients with Parkinson’s diseases. Besides, TIPE2 expression was also found to be strongly linked with the age of the patients [ 94 ] ( Figure 2 G).…”
Section: Role Of Tipe Family Of Proteins In Different Chronic Disementioning
confidence: 99%
“…Dopaminergic neuron loss is known as hallmark of PD (Sulzer, 2007). The different molecular mechanisms are responsible for the pathophysiology of PD, including microglia activation (Sarkar, Lu, Raymick, Hanig, & Gu, 2018), change in astrocytes (De Miranda et al, 2018), increase in oxidative stress (Monzani et al, 2018) and inflammatory cytokines (Kouchaki, Daneshvar Kakhaki et al, 2018;, aggregation of α-synuclein (W. Zhang et al, 2005), neurotransmission (Barone, 2010), synaptic plasticity (Pisani, Centonze, Bernardi, & Calabresi, 2005), adult neurogenesis (Marxreiter, Regensburger, & Winkler, 2013), brain lymphatic drainage system (B.-L. Sun et al, 2018), and changes in expression of aquaporins (AQPs; Badaut et al, 2008;Thenral & Vanisree, 2012).…”
Section: Introductionmentioning
confidence: 99%